Prevalence of Depression, Anxiety, and Stress Among University Students After the COVID-19 First Wave in Pakistan - Saeed, Wizra; Irfan, Saira; Zafar, Neelam; Cheema, Faiqa (Pakistan Journal of Humanities and Social Sciences, 2021)
COVID-19, the worst public health emergency in a decade, has had a profound impact on people's mental health. Universities in Pakistan have reopened, although it is uncertain how to prevent secondary damage to students as a result of the reopening. The purpose of this study was to determine the prevalence of depression, anxiety and stress among students following the reopening of universities after the COVID-19 first wave. Furthermore, gender differences in depression, anxiety, and stress were also investigated, as well as the predictive value of CGPA in depression, anxiety, and stress. The sample was (N=360) university students. Data was collected from the two cites of Pakistan. The DASS-21 was used to assess levels of depression, anxiety, and stress among students (Lovibond & Lovibond, 1995). SPSS version 21 was used to analyze the data. Results indicated that the level of psychological distress has increased among university students due to the reopening of universities. Findings revealed significant differences in depression and anxiety levels based on the three academic disciplines. In addition, male students showed significantly higher levels of depression, anxiety and stress than female students and CGPA significantly and negatively predicted depression and stress. Based on the findings of this study, it is suggested that thorough and targeted psychological interventions for students' mental health should be established, particularly in high-risk cities and during the COVID-19 pandemic late phases.